2012
DOI: 10.1159/000337720
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Electrical Nerve Stimulation Improves Low Back Pain during Pregnancy

Abstract: Background: To compare the efficiency of transcutaneous electrical nerve stimulation (TENS) with those of exercise and acetaminophen for the treatment of pregnancy-related low back pain (LBP) during the third trimester of pregnancy. Methods: This prospective study included 79 subjects (≥32 gestational weeks) with visual analog scale (VAS) pain scores ≥5. Participants were divided randomly into a control group (n = 21) and three treatment groups [exercise (n = 19); acetaminophen (n = 19); TENS (n = 20)]. The VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
16

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 49 publications
1
48
0
16
Order By: Relevance
“…In one-third of pregnant women, this pain is a severe problem and has an adverse effect on the quality of life. [8] For a pregnant woman presenting with low back pain, a detailed history and physical examination should be conducted. the goal is to exclude pregnancy-related back pain from other causes of pain such as UtI, osteomyelitis, sciatica, lumbar disk lesion or prolapse, arthritis of spine or hip, lumbar stenosis, cauda equina syndrome, spondylolisthesis, PS, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one-third of pregnant women, this pain is a severe problem and has an adverse effect on the quality of life. [8] For a pregnant woman presenting with low back pain, a detailed history and physical examination should be conducted. the goal is to exclude pregnancy-related back pain from other causes of pain such as UtI, osteomyelitis, sciatica, lumbar disk lesion or prolapse, arthritis of spine or hip, lumbar stenosis, cauda equina syndrome, spondylolisthesis, PS, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying conditions might be inflammatory, infectious, traumatic, neoplastic, degenerative, or metabolic. [8,9] Ostgaard et al investigated whether biomechanical factors such as weight gain, abdominal circumference measure, sagittal and transverse abdominal diameter, lumbar lordosis depth, and hyperlaxity affect pain development during pregnancy. they found that increase in sagittal abdominal diameter and lumbar lordosis depth are influential.…”
Section: Discussionmentioning
confidence: 99%
“…However, timing of acupuncture during preg- [86,87] . One study compared no treatment (control arm) to 3 intervention groups (exercise, acetaminophen and TENS respectively) and found TENS to be as effective as exercise and acetaminophen [88] .…”
Section: Complementary and Alternative Medicinementioning
confidence: 99%
“…Formulations that facilitate more rapid drug absorption may provide rapid pain relief and allow NSAID use with fewer adverse effects compared with traditional NSAIDs (Table 2) [94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]. Intranasal drug administration may provide a simple, noninvasive therapy that could allow for rapid pain relief following opioid [94,95] or NSAID administration with limited systemic exposure [113].…”
Section: New Therapeutic Options For the Management Of Acute Painmentioning
confidence: 99%
“…For example, muscular pain or dysmenorrhea and labor pain may be treated using transcutaneous electrical stimulation. A study of 79 patients suffering from low back pain in the third trimester of pregnancy found that transcutaneous electrical stimulation provided superior pain relief compared with acetaminophen [104], and a metaanalysis found that it reduced analgesic use in patients with postoperative pain [105]. However, the evidence for its efficacy in acute pain is not robust, and larger studies are needed [159].…”
Section: New Therapeutic Options For the Management Of Acute Painmentioning
confidence: 99%